INFLUENCE OF THE ACIDITY OF THE IODOUS ACID SOLUTION SYSTEM ON THE KINETICS OF THE DISPROPORTIONATION REACTION - Marković, Smiljana (Bulletin of Natural Sciences Research, 2021)
Influence of the acidity of the iodous acid (HOIO) solution system on the kinetics disproportionation reaction is  examined in aqueous sulfuric acid solution (0.125 moldm-3). The disproportionation reaction rate constants were determined at 285, 291, 298 and 303 K based on data obtained under  stationary conditions. The calculated rate constants increase  with increasing temperature for different values ​​of iodous acid and iodate concentrations. The average activation energy of 46 kJmol-1 was determined for the chosen temperature interval, by a graphical method.  The values ​​of pseudo-equilibrium concentrations of kinetically important and catalytic species H+, H2OI+ i IO3- in the disproportionation reaction were determined for the given experimental conditions based on the equilibrium dissociation reactions of sulfuric and iodous acids in the quasi-stationary state. The estimated values ​​of sulfuric and iodous acid are predominant and higher than the concentration of the protonated ion of H2OI+.
Keywords: Disproportionation reaction; Iodous acid; Activation energy; Rate constants; Kinetics